PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN DANA ZAKAT, INFAQ, SHADAQAH PSAK 109 DENGAN MICROSOFT EXCEL ACCOUNTING - Yekti Nilasari; Nidia Wulan Sari; Triani Patra Pertiwi; Intan Selliana; Cicin Cintia; Uus Usniyati (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
The Zakat Collection Unit (UPZ) At-Taqwa Cirebon City is an institution responsible for managing zakat, infak, and sadaqah (ZIS) funds, including their collection, management, and distribution to beneficiaries. However, the institution faces challenges related to limited understanding and inadequate human resource (HR) skills in accounting data management. As a result, financial reports are still prepared manually, making the process inefficient, ineffective, and often delayed. This Community Service Program (PKM) aims to provide training and assistance to UPZ At-Taqwa in preparing financial statements in accordance with the Financial Accounting Standards (PSAK) 109 on Accounting for Zakat, Infak, and Sadaqah. The implementation methods include socialization, lectures, interviews, and hands-on training sessions. The mentoring program focuses on utilizing a Microsoft Excel for Accounting System, a customized Excel-based system designed to facilitate transaction recording and financial report preparation quickly, neatly, and accurately. The training also covers the use of specific Excel formulas developed to support accounting processes for zakat institutions. The results of this program show a significant improvement in the UPZ At-Taqwa staff’s ability to prepare and manage financial reports using the Excel for Accounting system. Additionally, the efficiency, accuracy, and compliance of financial reporting with PSAK 109 standards have notably increased.